1969
DOI: 10.1073/pnas.62.2.536
|View full text |Cite
|
Sign up to set email alerts
|

The Purine Requirement of Cells Cultured From Humans Affected With the Lesch-Nyhan Syndrome (Hypoxanthine-Guanine Phosphoribosyltransferase Deficiency)

Abstract: Abstract.-Humans with the Lesch-Nyhan syndrome have an X-chromosomal mutant gene that causes severe neurological and developmental abnormalities. The patients are deficient in hypoxanthine-guanine phosphoribosyltransferase, which converts hypoxanthine to inosinic acid, a major precursor of adenine and guanine nucleotides. Paradoxically, the enzyme defect causes hypernormal de novo synthesis of inosinic acid, which manifests itself as excesses of hypoxanthine, xanthine, and uric acid. The first step in the de n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1970
1970
2008
2008

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Skewed patterns of XCI were initially found in female carriers of specific X-linked mutations (8,9) where skewing resulted from the negative selection of cells harboring the lethal allele in the active state. Skewing of XCI was also reported in rare cases of balanced X/autosome translocations, which perturbed the normal mechanisms of XCI (10).…”
Section: Introductionmentioning
confidence: 99%
“…Skewed patterns of XCI were initially found in female carriers of specific X-linked mutations (8,9) where skewing resulted from the negative selection of cells harboring the lethal allele in the active state. Skewing of XCI was also reported in rare cases of balanced X/autosome translocations, which perturbed the normal mechanisms of XCI (10).…”
Section: Introductionmentioning
confidence: 99%
“…Administered in subsequent studies to two maternal cousins of the twins who had clinical features of the L-N syndrome and absence of erythrocyte hypoxanthine-guanine phosphoribosyltransferase activity were adenine, 10 mg/kg/24 hr, adenine, 40 mg/kg/24 hr, folic acid, and monosodium glutamate. Low dose adenine had a slight suppressive effect on glycine-1- 14 C incorporation into uric acid; high dose adenine had a strong suppressive effect in the second patient. We conclude that the adenine dose chosen for therapy was too low.…”
mentioning
confidence: 84%
“…[29] demonstrated that control of hyperuricemia with allopurinol begun in the neonatal period in an effected patient did not alter the development of the L-N syndrome. We knew that adenine and folic acid enabled fibroblasts to grow in limiting media [14] and that adenine has renal toxicity in rats [34]. It was then decided to treat both twins with folic acid and twin A with adenine to test the hypothesis that one or both of these materials, started at birth, would affect development of central nervous system dysfunction.…”
Section: Rationale Of Therapymentioning
confidence: 99%
See 2 more Smart Citations